Structural analysis - Hibbeler, R. C. (Prentice Hall, 2005)
This text book is great for describing both the introductory and advanced methods of structural analysis, i.e. statically determinate/indeterminate structures and matrix methods. ASCE-7 is referenced quite frequently in the beginning chapters of the text. Colorful diagrams are present throughout the text to give the reader a better understanding of the material. The only negative aspect of this text book is that it does not describe two-way floor loading very well. Recommendations: anyone who has an interest in structural engineering